A free boundary seepage problem through earth dam withan impermeable screen - K. P. Kurtseva; E. G. Sheshukov; N. D. Yakimov (Известия высших учебных заведений: Проблемы энергетики)
A water seepage problem through the rectangular earth dam with the presence of a vertical impermeable screen was studied in nonlinear formulation. A finite-difference scheme with a fixed mesh was used for discretization of mathematical equations with a free boundary. The optimal position of the impermeable screen was found for its optimal length, that facilitates minimum losses of water. An analytical solution was developed in implicit form under the Darcy’s law formulation using the fragment’s method. The solution provides a relationship between water flux and a position of the screen.